Optimization of the Selection System in the Management of Admission of Excellent Students Based on Academic and Non-Academic Achievements in State Islamic High School Madrasah - Zakiah, Siti; Warisno, Andi; Asrori, Achmad; Abun, A. Rifa’i (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aims to develop an optimization model for the selection system in the management of outstanding student admissions based on academic and non-academic achievements in State Islamic Senior High Schools (Madrasah Aliyah Negeri) across Lampung Province, as well as to describe the current implementation of the selection system, analyze the constraints encountered, and examine optimization based on the principles of Islamic educational management. This research employs a qualitative approach with a multisite case study method conducted at Madrasah Aliyah Negeri 1 Bandar Lampung, Madrasah Aliyah Negeri 1 Metro, and Madrasah Aliyah Negeri Insan Scholar East Lampung, with data and data sources obtained from principals, teachers, educational staff, students, and supporting documents related to the research focus. With data collection techniques including in-depth interviews, observation, and documentation, while data analysis uses the interactive model of Miles and Huberman. The results indicate that the selection system has been implemented by integrating various instruments such as academic tests, report card scores, achievement portfolios, interviews, and digitalization; however, it is not yet fully optimal and standardized, with main constraints including non-uniform selection mechanisms, the absence of standardized assessment rubrics, limited committee competence, suboptimal digitalization, and low transparency. Therefore, optimizing the selection system requires strengthening the principles of justice, trustworthiness, honesty, professionalism, and public benefit in every stage of the selection process. The resulting model is an integrated selection system based on merit system, digitalization, and Islamic educational management values, with the conclusion that a standardized, objective, and value-based selection system can improve the quality of student input and enhance public trust in madrasas.